WGC Based Robust and Gain Scheduling PI Controller Design for Condensing Boilers. (22nd May 2014) - Onat, Cem
Abstract : This paper addresses the water temperature PI control in condensing domestic boilers. The main challenge of this process under the controller design perspective is the fact that the dynamics of condensing boilers are strongly affected by the demanded water flow rate. First, a robust PI controller based on weighted geometrical center method is designed that stabilizes and achieves good performance for closed-loop system for a wide range of the water flow rate. Then, it is shown that if the water flow rate information is used to update the controller gains, through a technique known as gain scheduled control, the performance can be significantly improved. Important characteristics of these PI design approaches are that the resulting parameters are calculated numerically without using any graphical method or iterative optimization process and that it guarantees the stability of the closed-loop. Significantly, simulation results have demonstrated that the proposed tuning techniques can perform better for set point changes and load disturbance than other available methods in the literature.